Histological Effects of Adding Gold to the Eggshell nHA and Seashell nHA on Rabbits Wound Healing - Banan N. Alhussary; Ghada A. Taqa; Amer A. Taqa (Al-Rafidain Dental Journal, 2020)
Aims:To evaluate the histological effect of the gold alone and gold with nanohydroxyapitite(nHA ) of (eggshell and seashell) on healing in the rabbit’s mandibular bone . Materials and Methods: twelve male rabbit were assigned to form four experimental groups and three animals in each groups, small groove was done in the rabbits mandibular bone: Group 1: control groups (groove was not filled by anything), Group 2: gold alone (groove was filled by gold), Group 3: eggshell nHA with 5% from gold (groove was filled with eggshell nHA with gold 5% ) and Group 4: seashell nHA with gold 5% from (groove was filled with seashell nHA with 5% from gold).Results: Histological study of adding the gold showed increasing in bone healing like space filling and newly formed bone trabeculi and highly number of lacuna compare with control groups while when adding the gold with nHA (eggshell and seashell) showed more enhancing in bone healing compare with control and gold alone. Conclusion: this study concluded that the addition of gold on nHA (eggshell and seashell) was successfully increasing in bone healing compare with control group.